Putting Federalism in Its Place - Greer, Scott L.; Béland, Daniel; Lecours, Andre; Dubin, Kenneth (University of Michigan Press, 2023)
What does federalism do to welfare states? This question arises in scholarly debates about policy design as well as in discussions about the right political institutions for a country. It has frustrated many, with federalism seeming to matter in all sorts of combinations with all sorts of issues, from nationalism to racism to intergovernmental competition. The diffuse federalism literature has not come to compelling answers for very basic questions.